Analytical thermal boundary condition for quasi-transient simulation of internal flow experiments - Forsyth, PR; Gillespie, D; McGilvray, M (American Institute of Aeronautics and Astronautics, 2021)
Transient thermochromic liquid crystal (TLC) experiments can provide high-fidelity spatially resolved heat transfer data for complex geometries, particularly where infrared techniques cannot be applied. One challenge when applying transient methods to internal geometries is the local definition of the driving gas temperature. The transient nature of the streamwise driving gas temperature profile has led to comparisons with steady-state computational fluid dynamics being questioned. This paper explores simulating the temporal behavior of transient TLC experiments directly. A novel technique is developed to account for differences in the gas and solid time scales, where surface temperature is calculated at each spatial location analytically from the surface heat flux, using an impulse response method assuming one dimensional, semi-infinite conduction. Postprocessing of the simulated surface temperature history is performed using the same method as experimentally, allowing for direct comparison. This analytical thermal boundary condition (ATBC) is applied to simulate a transient TLC experiment of a stationary superscaled rib turbulated internal cooling passage in a gas turbine engine. Traditional steady-state simulations were also performed with constant temporal and spatial temperature boundary conditions. Results show that calculations using the new ATBC and traditional steady-state method give very similar Nusselt number distributions and mean values in relation to the experimental data, suggesting the larger discrepancy between simulations and the experiments is not the definition of the driving gas temperature. Analysis of transient variation of Nusselt number indicated brief highly localized maximum variations up to 40%, although this was not found to significantly affect the mean values, and passage-averaged values converged to within 0.5% of the final value within 0.2 s.